Pengembangan Alat Peraga IPA dari Barang Bekas Untuk Meningkatkan Minat dan Motivasi Belajar Siswa SMP - Pratiwi, Zuliana Eka; Pramesti, Salsabila Aprillyanti; Rosidah, (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA DAN SAINS, 2022)
There are still a few simple teaching aids available for studying Pascal's law and hydrostatic pressure. The development of teaching aids in the form of a “mini dispenser” is intended to help students understand more in real terms and details related to Pascal's law and hydrostatic pressure. In addition, "mini dispenser" props from used goods can increase students' interest and motivation and so that learning is not abstract, so that student learning outcomes can increase. The mini dispenser model itself can be made from used or new goods. The data in this study were obtained from a questionnaire that measured the interest and motivation of students after using teaching aids. The participants involved in this study were 10 students. The results showed that the majority of students' interests and motivations were positive towards the developed teaching aids. The results of this survey indicate that the science teaching aid in the form of a mini dispenser is good from the aspect of stimulating the interest and motivation of students in science learning. Keywords: teaching aid, interest, motivation